Thin Films: Combined Experimental and Computational Methods Reveal the Evolution of Buried Interfaces during Synthesis of Ferroelectric Thin Films (Adv. Mater. Interfaces 10/2015). Issue 10 (6th July 2015) - Jones, Jacob L.; LeBeau, James M.; Nikkel, Jason; Oni, Adedapo A.; Dycus, J. Houston; Cozzan, Clayton; Lin, Fang‐Yin; Chernatynskiy, Aleksandr; Nino, Juan C.; Sinnott, Susan B.; Mhin, Sungwook; Brennecka, Geoff L.; et al.
<x xml:space="preserve">Abstract</x> Scanning transmission electron microscopy is utilized to reveal atomic‐level interactions that occur during thermal processing at thin film oxide‐metal interfaces, as described by J. L. Jones and co‐workers in article 1500181. These observations, combined with in situ X‐ray diffraction and theoretical techniques, are used to determine how solution‐processed lead zirconate titanate (PZT) films nucleate on Pt electrodes, results that will guide future ferroelectric film processing.